ChemInform Abstract: The Benzoyl Peroxide‐Promoted Functionalization of Simple Alkanes with 2‐Aryl Phenyl Isonitrile. Issue 3 (January 2015) - Sha, Wanxing; Yu, Jin‐Tao; Jiang, Yan; Yang, Haitao; Cheng, Jiang
Abstract leading to a variety of phenanthridines